Pengaruh Kompetensi, Motivasi, Dan Disiplin Kerja Terhadap Kinerja Pekerja Proyek Konstruksi di Kabupaten Garut - Ganjar Jojon Johari; Rendi Alfarez (Jurnal Konstruksi, 2026)
In the implementation of construction projects in Garut Regency, the role of human resources is critically important. Human resources are one of the main factors determining the success or failure of a construction project. Project quality and productivity are highly dependent on human resource aspects, namely competence, motivation, and work discipline of the workforce involved. This study aims to determine the extent to which competence, motivation, and work discipline influence the performance of construction project workers. The research employs a quantitative method, with multiple linear regression analysis as the analytical approach. Data analysis was conducted using SPSS version 29. The results of the partial t-test indicate that competence does not have a significant effect on worker performance (t-value 0.278 < t-table 2.056), while motivation has a significant effect on performance (t-value 3.292 > t-table 2.056), and work discipline also has a significant effect on performance (t-value 3.141 > t-table 2.056). Simultaneously, competence, motivation, and work discipline collectively have a significant influence on the performance of construction project workers.